The Impact of CHSE (Cleanliness, Health, Safety, and Environmental Sustainability) on Tourist Satisfaction Levels and Revisit Intentions in Dusun Semilir, Semarang Regency - Ronald Mahendra Jati; I Ketut Antara; Putu Sucita Yanthy (Return : Study of Management, Economic and Bussines, 2024)
There was a drastic decline in the number of tourists in 2020 and 2021 due to the COVID-19 virus. This situation encourages tourist destination managers to find and formulate the best strategies to survive and recover from this difficult situation. One of the policies implemented by the manager is the implementation of CHSE. The purpose of this study is to investigate the relationship between CHSE and the satisfaction and intention of tourists to return to Semilir Hamlet. This research is included in the quantitative category. Data sources were obtained through interviews and questionnaire distribution. The sampling method used was purposive sampling, resulting in 108 respondents. The data analysis technique was carried out using Smart PLS software. The results showed that the CHSE variable had a significant influence on the intention to return to visit. In addition, the CHSE variable also contributes positively and significantly to tourist satisfaction. Furthermore, the level of tourist satisfaction has a positive and significant effect on the intention to return to Semilir Hamlet. The results of the analysis show that the CHSE variable has a positive and significant impact on the intention to visit again through tourist satisfaction. Thus, it can be concluded that the implementation of CHSE has a great influence on tourist satisfaction and their intention to visit Semilir Hamlet again.